2016
DOI: 10.1245/s10434-016-5274-4
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Resection for Metastatic Neuroendocrine Cancer in Patients with Bone Metastases

Abstract: The present study is the first report to describe HR for patients with metastatic NET and known bone metastases. We demonstrated that in properly selected cases, excellent survival can be achieved with liver debulking in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Prior studies have suggested that surgical resection of the primary tumor without metastasectomy [23][24][25][26][27] and liver metastasectomy alone [28][29][30][31] both independently provide a survival benefit. Current NCCN guidelines also recommend complete resection of metastatic disease if possible [32].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have suggested that surgical resection of the primary tumor without metastasectomy [23][24][25][26][27] and liver metastasectomy alone [28][29][30][31] both independently provide a survival benefit. Current NCCN guidelines also recommend complete resection of metastatic disease if possible [32].…”
Section: Discussionmentioning
confidence: 99%
“…The median survival was 73.3 months for patients with liver and bone metastases from GI NET. 14 Analysis of NEN survival rates from the SEER database found that the median overall survival (OS) for all NEN patients was 9.3 years in the United States. Well-differentiated 2 Clinical Medicine Insights: Endocrinology and Diabetes tumors were found to have higher OS than moderately differentiated tumors (16.2 vs 8.3 years).…”
Section: Epidemiologymentioning
confidence: 99%
“…In a systematic review, Saxena et al noted that poor histologic grade, extrahepatic disease, and a macroscopically incomplete resection were negative prognostic factors (21). While extrahepatic metastatic disease is one of the most consistent prognostic factors observed across studies, hepatic resection in the setting of low-volume indolent bone metastases may be appropriate (30). In addition, synchronous disease is associated with higher recurrence rates compared with metachronous disease (31).…”
Section: Prognostic Factorsmentioning
confidence: 99%